The Activity Of The Participants Of The Freedom Movement In The Territory Of The Surkhan Oasis In The Struggle Against The Soviet Authorities - Mengliboev, Akmal Kholtorayevich (Peerian Journals Publishing, 2024)
In this article, we will see the activities of individuals who participated in the national liberation movements in Surkhandarya region, i.e. Ibrohimbek, Turdi Toksabo, Berdi Abdurazzok, Otanbek and others. However, due to the death of Anwar Poshho and the departure of Salim Poshho to Afghanistan, the movement against the Red Army in Bukhara once again had its only commander in the person of Ibrahimbek. In addition, we will get information about how the liberation movement against the Soviet occupation took place in the Surkhan oasis and in which areas the battles were fought
Keywords: Turdi toksabo; Berdi Abdurazok; Bobotog skirts